MISDINAR SEBAGAI WADAH PENDAMPINGAN IMAN DAN PENERAPAN TRADISI KATOLIK: (STUDI KASUS DI GEREJA ST. ATHANASIUS AGUNG, KARANGPANAS, SEMARANG) - Cahyaningtias, Maria Charisma Dewi; Sugiyana, Sugiyana; Wuriningsih, FR. (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2023)
Understanding and implementing Catholic Tradition is essential for a Misdinar. This research focuses on examining the comprehension and application of Catholic Tradition by Misdinar members at St. Athanasius Agung Karangpanas Church in Semarang, the Faith Formation, especially regarding Catholic Tradition within Misdinar, and the role of parents also the Parish Priest in participating in the Faith Formation of Misdinars. This research was conducted in May 2023 at St. Athanasius Agung Karangpanas Church, Semarang, using triangulation techniques to gather data. The findings reveal that Misdinar members understand about Catholic Tradition and can apply it effectively. Faith Formation for Misdinars has proven effective for nurturing faith, particularly in Catholic Tradition, through training, teachings about Catholic Tradition, group prayers, and devotions at Misdinar community. Nonetheless, the study recommends variations in carrying out Faith Formation to prevent Misdinar from feeling bored. Furthermore, the involvement of parents and the Parish Priest have a important role for faith formation of Adolescent. Further efforts are needed to increase their participation in supporting the Faith Formation for Misdinar. In conclusion, the cooperation of the entire church community is essential in accompanying the Misdinar faith and their ability to be role models in the wider church community. Keywords: Adolescent, Catholic Tradition, Faith Formation, Misdinar.